2003
DOI: 10.1073/pnas.1135965100
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of neuropeptide Y (NPY) 2 receptor in mice results in blockage of NPY-induced angiogenesis and delayed wound healing

Abstract: Neuropeptide Y (NPY), a 36-aa peptide, is widely distributed in the brain and peripheral tissues. Whereas physiological roles of NPY as a hormone͞neurotransmitter have been well studied, little is known about its other peripheral functions. Here, we report that NPY acts as a potent angiogenic factor in vivo using the mouse corneal micropocket and the chick chorioallantoic membrane (CAM) assays. Unlike vascular endothelial growth factor (VEGF), microvessels induced by NPY had distinct vascular tree-like structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
152
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(156 citation statements)
references
References 44 publications
4
152
0
Order By: Relevance
“…Stimulation of angiogenesis can enhance healing rates, [27][28][29][30][31][32][33] whereas a reduction in angiogenesis can impair the same. [34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury. [29][30][31] In contrast, several reports have shown that modulation of angiogenesis does not affect epidermal healing rates or overall wound closure to a great degree, [38][39][40][41][42][43] and some studies have even reported enhanced healing with reduced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of angiogenesis can enhance healing rates, [27][28][29][30][31][32][33] whereas a reduction in angiogenesis can impair the same. [34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury. [29][30][31] In contrast, several reports have shown that modulation of angiogenesis does not affect epidermal healing rates or overall wound closure to a great degree, [38][39][40][41][42][43] and some studies have even reported enhanced healing with reduced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that during development, peripheral nerves have a role in determining the organ-specific patterns of blood vessel branching and arterial maturation (5). Furthermore, some neuronal factors such as Notch and neuropeptide Y were reported to have roles in tumor-associated angiogenesis (6,7).…”
mentioning
confidence: 93%
“…Chorioallantoic membrane assay (CAM) was performed as described (28,29). Briefly, fertilized Leghorn chicken eggs were incubated under conditions of constant humidity (60%) at 37°C for 72 h. On days 3-4, eggs were opened into sterile clingwrap hammocks and incubated at 37°C with 2.0% CO 2 and 90% relative humidity for 4 more days.…”
mentioning
confidence: 99%